Pengaruh Kinerja Keuangan, Profibilitas Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia - Lita Suwasyono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to analyze the effect of financial performance, profibility, and capital structure on company value in LQ45 companies listed on the Indonesia Stock Exchange. This study used quantitative methods. Sampling is done using the purposive sampling method which means the sample is selected based on certain considerations. The data used are financial statements obtained through https://old.idx.co.id/ website. In this study only data that met the criteria and needs of the authors were used as samples. The results of the study stated that financial performance had a significant effect on company value, it can be seen from T for financial performance variables is 0.608 0.05, profitability has a significant effect on company value, seen from the calculated value for profitability variables is 0.935 0.05, capital structure has a significant effect on company value, can be seen from the calculated value for the capital structure variable is 0.633 0.05, and the F test is used to determine the influence of independent variables simultaneously (together) can be seen from the statistical value of F value is 0.155 F value is 0.926 greater than 0.05 then it has no effect on the value of the company.The results of the above research can then be drawn 4 conclusions, namely: 1. Financial performance does not have a significant effect on the value of the company. 2. Profitability has no significant effect on the value of the company. 3. Capital structure has no significant effect on the value of the company. 4. Financial performance, profitability, and capital structure on company value have no effect on company value.LQ45 is listed on Indonesia Stock Exchange.